HISTIOCYTE RICH PSEUDOTUMOUR OF SPLEEN/SPLENIC LYMPH NODE AFTER CHEMOTHERAPY FOR ACUTE LYMPHOBLASTIC LEUKEMIA A CASE REPORT: Acute Lymphoblastic Leukemia - Ahmed, Rabia; Ghafoor, Tariq; Akhtar, Farhan; Hashmi, Shoaib Naiyar; Din, Hafeez -ud-; Jamal, Shahid (Pakistan Armed Forces Medical Journal, 2014)
Post chemotherapy histiocyte-rich pseudotumour of spleen and lymph node are a rare occurrence and can be seen in patients after chemotherapy of haematological malignancies. We report the case of a two years old child, a diagnosed case of Acute Lymphoblastic Leukemia under going chemotherapy. He presented to the paediatric oncology department of Combined Military Hospital, Rawalpindi for follow up examination. Clinical examination and ultrasound abdomen revealed splenomegaly. Haematological investigations revealed worsening of blood counts. Splenectomy was planned in order to improve hypersplenism and to evaluate leukemic infiltration of spleen. Spleen and a perihilar lymph node were removed surgically and the specimens were sent to the histopathology department of Armed Forces Institute Pathology, Rawalpindi. Histologically, spleen and lymph node showed sinus dilatation and infiltration by numerous macrophages, which were positive for histiocytic immunohistochemical markers. On the basis of histopathological and immunohistochemical features, the diagnosis of post chemotherapy histiocyte-rich pseudotumour of spleen and lymph node was made.